Cooperative Learning Strategy for Improving Studentsâ Critical Reading Ability: A Case Study in English Study Program of Brawijaya University - Sudarwati, Emy; Manipuspika, Yana Shanti (EDUCARE, 2016)
ABSTRACT: This study deals with a strategy named GD (Group Discussion) model of cooperative learning strategy applied in the teaching of critical reading course at English Study Program at the UNIBRAW (Brawijaya University) in Malang City, East Java, Indonesia. By using that strategy, it is expected that the problem in Critical Reading class can be solved and studentsâ ability in critical reading will, in turn, be improved. The design of the study is CAR (Classroom Action Research), since the study is aimed at improving the studentsâ critical reading ability and solving the classroomâs problems on the teaching of reading. Based on its characteristics, the CAR is done repeatedly until those problems can be solved. Dealing with the classroom setting, the study is directed to develop the teaching strategy in order to find out a solution to the classroomâs problem in the teaching of reading. This study reveals that cooperative learning strategy has successfully improved studentsâ critical reading ability. In doing so, there are stages conducted, namely: having cooperative work organization, using appropriate media, having creativity (for teachers), monitoring teaching and learning processes closely, and giving students feedback on their work. In conclusion, cooperative learning can be beneficial for studentsâ learning in critical reading as it can make students active and enjoy the classroom activities. However, it also has weaknesses, such as time consuming and less appropriate for classes with bigger number of students. Despite the weaknesses, teachers are still recommended to apply this strategy in Critical Reading classes.KEY WORDS: Critical Reading; Studentsâ Ability; Cooperative Learning; Group Discussion; Classroom Action Research.Â Â About the Authors: Emy Sudarwati and Yana Shanti Manipuspika are the Lecturers at the Study Program of English, Faculty of Humanities UNIBRAW (Brawijaya University) in Malang City, East Java, Indonesia. For academic interests, the authors can be contacted via e-mail at: yana.manipuspika@gmail.comHow to cite this article? Sudarwati, Emy & Yana Shanti Manipuspika. (2016). âCooperative Learning Strategy for Improving Studentsâ Critical Reading Ability: A Case Study in English Study Program of Brawijaya Universityâ in EDUCARE: International Journal for Educational Studies, Vol.9(1) August, pp.13-28. Bandung, Indonesia: Minda Masagi Press owned by ASPENSI, ISSN 1979-7877. Chronicle of the article: Accepted (January 22, 2016); Revised (May 20, 2016); and Published (August 30, 2016).